The answer is 0.5.
X is the input and f(x) is the output. Between -3 and -2 the difference is 0.5. Because it goes from -0.5 to 1
Answer:
(5x² + 3) (2x-3)
Step-by-step explanation:
10x³ - 15x² + 6x - 9 (rearrange)
10x³+ 6x - 15x² - 9 (group using parentheses)
(10x³+ 6x) - (15x² + 9) (factor out 2x from first term and 3 from second term)
2x (5x²+ 3) - 3(5x² + 3) (factor out (5x²+3) )
(5x² + 3) (2x-3) (answer)
Answer:4
Step-by-step explanation: Because 4 goes in 3/4 better and more eqvilent to that answer.
1. You con solve the quadratic equation x^2+20x+100=50<span> by following the proccedure below:
2. Pass the number 50 from the right member to the left member. Then you obtain:
x^2+20x+100-50=0
</span><span> x^2+20x+50=0
</span><span>
3. Then, you must apply the quadratic equation, which is:
x=(-b±√(b^2-4ac))/2a
</span><span>x^2+20x+50=0
</span><span>
a=1
b=20
c=50
4. Therefore, when you substitute the values into the quadratic equation and simplify ir, you obtain that the result is:
-10</span>±5√2 (It is the last option).